Synthesis and Characterization of Silica-Thioamide Hybrid Compounds Derived from Rice Husk Ash with Expected Biological and Catalytic Activity - Hayder Hamied Mihsen (Journal of Global Pharma Technology, 2018)
The thiosemicarbazide (TSC) and thionicotinamide (TNA) were immobilized onto silica extracted from RH (rice husk) using 3-chloropropyltriethoxysilane (CPTES) forming solid organic-inorganic hybrid compounds labeled as RHACTSC and RHACTNA, respectively. The BET data of the new compounds reported that the surface area for RHACTSC and RHACTNA to be 240 m2g-1 and 153 m2g-1 with an average pore diameter of 4.63 nm and 5.25 nm, respectively. The analysis of CHNS and FT-IR spectra revealed that the thiosemicarbazide and thionicotinamide have successfully incorporated on RHACI. The amorphous nature of RHACTSC and RHATN was investigated using X-ray diffraction technique, while the scanning electron microscope (SEM) technique showed that the surface was smooth with white rocky shape particles. Thermogravimetric analysis (TGA) of RHACTSC and RHACTNA indicate that the disappearance of physical adsorb water between 25- 217 °C, while at 588°C the residual parts of materials were decomposed.Keywords Rice husk ash; thiosemicarbazide ; thionicotinamide; organic-inorganic hybrid ; surface area.